Analysis of surface morphology and topography of pure aluminium machined using WEDM. (January 2018) - Mouralova, K.; Kovar, J.; Klakurkova, L.; Bednar, J.; Benes, L.; Zahradnicek, R.
Abstract: Wire electrical discharge machining (WEDM) represents the effective technology of unconventional machining used for the manufacture of components with complex shapes, for machining of hard materials following heat treatment or of non-ferrous metals that are difficult to machine with conventional processes. One non-ferrous material is pure aluminium 99.5 which is used for this experiment: for the design of the experiment, machine parameters were setup for the fabrication of 33 samples aluminium 99.5. The objective of this study was to find the key parameters of machine setup for the manufacture of high-precision components with the required surface quality. For this purpose, an analysis of the morphology of the surface layer was made using electron microscopy (SEM), including a local analysis of the chemical composition (EDX). In addition, the surface topography using 3D profilometer and profile and area parameters of the surface quality were evaluated, including 3D colour filtered and unfiltered images of surfaces taken using light microscopy. The prepared metallographic preparations allowed an analysis of the sub-surface area, including a local chemical microanalysis of "recast layer" using EDX. This study discovered the optimal setting of machining parameters (gap voltage = 70 V, pulse on time = 6 µs, pulse off time = 50 µs, discharge current = 25 A and wire feed = 14 m·min −1 ) for the best quality of machined surface and the narrowest width of kerf for precision machining.